1988
DOI: 10.1148/radiology.166.2.2827232
|View full text |Cite
|
Sign up to set email alerts
|

Localization of pancreatic insulinoma: comparison of pre- and intraoperative US with CT and angiography.

Abstract: Methods of preoperative radiologic localization of insulinoma were compared in 52 patients, 44 of whom had solitary tumors. Examinations performed in these 44 patients were preoperative ultrasonography (US) in 28, angiography in 26, and computed tomography in 23. Prospective sensitivities were 61%, 54%, and 30%, respectively. Imaging sensitivities were lower for the eight patients with multiple insulinomas. In 28 of the 44 patients, intraoperative US was performed without the examiner being aware of the surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
2
18

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(98 citation statements)
references
References 0 publications
2
76
2
18
Order By: Relevance
“…Doherty et al (27) have identified 64% of insulinomas by means of palpation. Machado et al (16) have reported the detection of 98.2% of cases by means of inspection/palpation, a result similar to those of other authors (35)(36)(37) . The literature review demonstrates that smaller the lesions to be evaluated, the greater will be the limitations of preoperative examinations.…”
Section: Introductionsupporting
confidence: 81%
“…Doherty et al (27) have identified 64% of insulinomas by means of palpation. Machado et al (16) have reported the detection of 98.2% of cases by means of inspection/palpation, a result similar to those of other authors (35)(36)(37) . The literature review demonstrates that smaller the lesions to be evaluated, the greater will be the limitations of preoperative examinations.…”
Section: Introductionsupporting
confidence: 81%
“…Preoperative localization studies using extracorporeal ultrasound, CT, and angiography fail to localize the primary tumor in 40 -60% of patient, and frequently miss small tumors (Ͻ2 cm) (5,6). Recently, arterial stimulation of the tumor with the appropriate secretagogue followed by selective portal venous sampling, has improved localization sen-sitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…48 In several series its sensitivity in localizing insulinoma is higher than 90% and considered superior to preoperative imaging studies, it being able to detect lesions as small as 2-3mm. 15,[49][50][51] It is hence is easy to understand that in laparoscopic surgery where there is typically a loss of tactile sensation, IOUS gains even greater importance with results being comparable to IOUS in open surgery. [52][53][54] A lack of laparoscopic IOUS, despite positive preoperative identification, has been cited as an important factor in the failure to intraoperatively identify lesions leading to increased incidences of conversion to open procedure.…”
Section: Localization Of the Tumormentioning
confidence: 99%